Effects of heating rate and heating up time to central biomass particles for bio-oil production - Ahmed, MB; Hasan, ATMK; Mohiuddin, M; Asadullah, M; Rahman, MS; Khaleque, A (Bangladesh Journal of Scientific and Industrial Research, 2016)
Objective of this work was to pyrolysis woody biomass. Experiments were carried out at 300 to 500oC. Relatively bigger particles were used. Special emphasis was given to investigate the effects of heating rate and heating up time of the central mass of the particles on the product distribution. Surface temperature reached to the reactor set temperature immediately while the temperature at the central part was as low as 50oC. The center temperature gradually increased to the final temperature within 3 to 8 minutes, depending on the wood types and the reactor set temperature. For ipil-ipil wood the heating rate of the central mass was much faster than krishnachura and koroi woods, and thus the heating up time was lower. Ipil-ipil wood was experienced higher yield (65%) even at lower reactor temperature 300oC with particle temperature 450oC. In the case of krishnachura and koroi woods, the bio-oil yields were lower under the same condition due to the heating rates of the central parts were much slower. Further researchon different biomasses may be necessary to demonstrate overall process. Bangladesh J. Sci. Ind. Res. 51(1), 13-22, 2016